FISIKA SOSIAL DAN PENYOALAN EKSISTENSI AGAMA DALAM POSITIVISME AUGUSTE COMTE, DAN KEMUNGKINAN RELEVANSINYA PADA DISKURSUS SOSIOLOGI AGAMA - Alim Roswantoro (Jurnal Sosiologi Agama, 2022)
This paper focuses on rethinking with epistemological analysis of the idea of social physics in Auguste Comte’s positivism which negates the existence of religion or theology. His imagined social physics replacing theology to find an objective-positive social theory did not completely deprive him of his inspiration from religious morality. Altruism, in his natural religion, humanism, is evidence of inspiration from religious morality, which he imagined as a universal-objective human value for overcoming social conflicts. In the future, sociology with its scientific method will find positive-objective social theories, such as altruism in his religion of humanism, as a scientific instrument to build the social cohesion of a society. Modern society, which he considered to be inhabited only by secular-scientific people, until now is in fact also inhabited by religious-scientific people. Rejecting the assumption that there is no relevance between Comte’s sociology and the sociology of religion, this paper emphasizes that there is relevance. Religious human social behavior as a social fact, not a doctrine of belief, can be observed, experimented with and compared to find the objectivity of social theory of religious social behavior which can also universalized as in Comte’s secular sociology.